Endophytic Bacteria of Pemphis acidula on Karst Ecosystem of Gorontalo, Indonesia - Yuliana Retnowati; Dewi Wahyuni K Baderan; Ramli Utina (Indonesian Society for microbiology, 2023)
Wild plant Pemphis acidula in coastal habitats is often associated with microbes on their root, stem, or leaf. The objective of the study was to reveal the endophytic bacteria associated with Pemphis acidula in the coastal area of Gorontalo, the study antibacterial activity of endophytic bacteria against pathogenic bacteria, and identify endophytic bacteria based on molecular characteristics. The Pemphis acidula sampling was conducted on three coastal areas of Gorontalo, including Biluhu beach, Dulanga beach, and Olele beach. The sample consists of the root, stem, and leaf of Pemphis acidula. The result showed that the endophytic bacteria were just found on the leaf. There were four isolates with similar morphological features. The antibacterial activity on a broad spectrum of two endophytic bacteria against both Escherichia coli and Staphylococcus aureus, whereas two isolates others on a narrow spectrum against Staphylococcus aureus. The endophytic bacterial identify as Bacillus tequilensis based on 16S rRNA gene sequence and this isolate is closely related to Bacillus tequilensis strain 20Q9-B-4-13 OK653944.1.37-1458 on a similarity index of 100%.